Answer:
y = 2(x-3)^2-2
Explanation:
We can find the quadratic equation by using the vertex form. The vertex form of a quadratic equation is:
, where x and y are any point on the parabola, a is the constant (indicating whether the parabola opens up or down), and h and k are the coordinates of the vertex.
Since we already have the y-int (an x and y coordinate lying on the parabola) and the vertex, we can plug in both to find a:
![16=a(0-3)^2-2\\16=a(-3)^2-2\\16=9a-2\\18=9a\\2=a](https://img.qammunity.org/2023/formulas/mathematics/college/rt0v3o2d08pxqwjxq5fyrvk6fv5b43bfcr.png)
Thus, the equation is:
![y=2(x-3)^2-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/xaj29ry8ljko58g0zabu6lhuwabmu37n8h.png)